Active Optimization of Binluh by Bhabinkamtibmas to Prevent Theft in the Legal Area of ​​Gresik Police - Firdaus, Baihaqi Ahmad (Indonesian Journal of Police Studies, 2024)
Gresik regency is an industrial area so that economic development has increased significantly and the population has increased every year. This has resulted in social disparities that have led to criminal acts. The crime of curanmor is a crime of concern because in the last three years it has always increased. The police have made several efforts to reduce this, one of which is through bhabinkamtibmas by carrying out coaching and counseling activities. This is the background for the author to find out what factors influence the implementation and how to opmtimize binluh activities. This research uses SWOT analysis theory and management theory and uses the concept of guidance and counseling, the concept of optimization approach with the type of field research and data collection technques with interviews, observation dan document studies. In this writing the author concludes that in the implementation of coaching and counseling activities there are still several obstacles tha result in the implementation of activities that are not optimal. Several efforts can be made, one of which is by applying the pattern of monitoring villages, touch villages and assisted villages.